2011
DOI: 10.1088/0004-637x/738/2/182
|View full text |Cite
|
Sign up to set email alerts
|

Stable Heating of Cluster Cooling Flows by Cosmic-Ray Streaming

Abstract: We study heating of cool cores in galaxy clusters by cosmic-ray (CR) streaming using numerical simulations. In this model, CRs are injected by the central active galactic nucleus (AGN) and move outward with Alfvén waves. The waves are excited by the streaming itself and become non-linear. If magnetic fields are large enough, CRs can prevail in and heat the entire core because of a large Alfvén velocity. We find that the CR streaming can stably heat both high and low temperature clusters for a long time without… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 80 publications
1
33
0
Order By: Relevance
“…For the radial dependence of the CR density, we first assume that the CR follow the same radial distribution as the thermal gas (referred to as the "isobaric" case). As alternative possibilities, we also consider a profile where the CR-to-thermal energy ratio increases with radius as ǫ(r) ∼ r 0.5 (referred as "flatter"), as expected from the acceleration of CR at cosmological shocks (see e.g., Vazza et al 2012;Pinzke & Pfrommer 2010;Donnert et al 2010), and a decreasing radial profile (ǫ(r) ∼ r −0.5 , referred as "steeper") to model the injection of CR by a central AGN (e.g., Colafrancesco & Marchegiani 2008;Mathews 2009;Fujita & Ohira 2011). Finally, upper limits on the CR energy density were derived for the three different cases and compared with the average thermal energy in our population, which was computed using the parameters given in Chen et al (2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the radial dependence of the CR density, we first assume that the CR follow the same radial distribution as the thermal gas (referred to as the "isobaric" case). As alternative possibilities, we also consider a profile where the CR-to-thermal energy ratio increases with radius as ǫ(r) ∼ r 0.5 (referred as "flatter"), as expected from the acceleration of CR at cosmological shocks (see e.g., Vazza et al 2012;Pinzke & Pfrommer 2010;Donnert et al 2010), and a decreasing radial profile (ǫ(r) ∼ r −0.5 , referred as "steeper") to model the injection of CR by a central AGN (e.g., Colafrancesco & Marchegiani 2008;Mathews 2009;Fujita & Ohira 2011). Finally, upper limits on the CR energy density were derived for the three different cases and compared with the average thermal energy in our population, which was computed using the parameters given in Chen et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…While the general picture is clear, the details of the heat transfer mechanism are still not understood. One of the proposed mechanisms (e.g., Colafrancesco & Marchegiani 2008;Mathews 2009;Fujita & Ohira 2011) considers the interaction of a population of relativistic CR with the gas as heat conveyor. In this framework, it has been shown that the observed Xray properties can be recovered if the CR energy density is large enough.…”
Section: Agn Feedback In Cool-core Clustersmentioning
confidence: 99%
“…Cosmic rays (CRs) can provide additional pressure support to gas, drive galactic outflows, and heat the CGM/ICM directly via hadronic and streaming losses (Guo & Oh 2008;Sharma et al 2010;Enßlin et al 2011;Fujita & Ohira 2011;Wiener et al 2013;Fujita et al 2013;Ruszkowski et al 2017a,b;Pfrommer 2013;Pfrommer et al 2017a;Jacob & Pfrommer 2017a,b;Jacob et al 2018). As a result several of the studies above suggest they can help quench star formation; however this is usually in the context of CRs from AGN.…”
Section: Cosmic Rays (Not From Agn)mentioning
confidence: 99%
“…Similarly, strong shocks are produced in jets from active galactic nuclei and they release large amounts of CRs as observed in radio emission (Fanaroff & Riley 1974;Pierre Auger Collaboration et al 2007;Croston et al 2009), and help to release the feedback back to the hot gas from galaxy clusters (Croston et al 2008;Guo & Oh 2008;Sijacki et al 2008;Guo & Mathews 2011;Fujita & Ohira 2011;Jacob & Pfrommer 2017;Ruszkowski et al 2017a;Ehlert et al 2018). However, again, their impact might significantly differ depending onto which CR dynamical processes are modeled and ignored.…”
Section: Introductionmentioning
confidence: 99%